Exploring the Causal Relationship and Molecular Mechanisms Between Fasting Insulin and Androgenetic Alopecia: A Mendelian Randomization Study with Bioinformatics Analysis - Ding X; Bai Z; Wang W; Gu Y; Li Z; Fan Y (Clinical, Cosmetic and Investigational Dermatology)
Xiaoxia Ding,1,* Zicheng Bai,2,* Wenwen Wang,2 Yu Gu,3 Zhiming Li,2 Yibin Fan1 1Center for Plastic & Reconstructive Surgery, Department of Dermatology, Zhejiang Provincial People’s Hospital (Affiliated People’s Hospital), Hangzhou Medical College, Hangzhou, Zhejiang, People’s Republic of China; 2Department of Dermatology and Venereology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 3Department of Dermatology, The First People’s Hospital of Aksu Prefecture, Aksu, XinJiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yibin Fan, Email fanyibin@hmc.edu.cn; Zhiming Li, Email zhi-mingli@wmu.edu.comBackground: Prior studies have suggested a significant connection between fasting insulin (FI) and androgenetic alopecia (AGA), but the exact cause of this connection and underlying molecular mechanism has not been clarified. In this study, a Mendelian randomization (MR) analysis was utilized to discover the causal associations between FI and AGA.Methods: Genome-wide association study (GWAS) data for FI and AGA were retrieved, and bidirectional MR analysis was conducted. FI-associated genes were identified through expression quantitative trait loci (eQTL) analysis, with enrichment analysis and a protein-protein interaction (PPI) network used to explore potential pathways and core genes.Results: Forward MR analysis revealed a significant causal relationship between elevated FI levels and AGA (P=0.027, OR=43.944). Reverse MR analysis found no causal effect of AGA on FI (P=0.808, OR=1.0001). A total of 92 FI-associated genes were analyzed, with enrichment results indicating involvement in glycine, serine, and threonine metabolic pathways. EIF2B4 and NRBP1 were identified as potential core genes linking FI and AGA.Conclusion: By using MR analysis, this study verified the possible causative connection between FIns and AGA by MR analysis. The core genes EIF2B4 and NRBP1, along with biological processes such as glycosylation and amino acid metabolism, may serve as crucial links.Keywords: androgenetic alopecia, fasting insulin, Mendelian randomization, GWAS, bioinformatics